Solid-State Fermentation With Aspergillus cristatus Enhances the Protopanaxadiol- and Protopanaxatriol-Associated Skin Anti-aging Activity of Panax notoginseng - Lee, Sunmin; Reddy, Chagam Koteswara; Ryu, Jeoung Jin; Kyung, Seoyeon; Lim, Yonghwan; Park, Myeong Sam; Kang, Seunghyun; Lee, Choong Hwan (Frontiers in Microbiology, 2021)
A metabolomics approach was used to profile metabolites of Panax notoginseng fermented with Aspergillus cristatus in two ways, liquid-state fermentation (LF-P) and solid-state fermentation (SSF-P) and examine metabolite markers representing antioxidant activity and skin anti-aging. Protopanaxadiol (PPD) and protopanaxatriol (PPT) contents were higher in SSF-P than in LF-P and showed a multiplicative increase over the fermentation period of four days. PPD and PPT levels also correlated with antioxidant and anti-aging effects in skin, based on the mRNA expression of dermal extracellular matrix components. In the bioactivity validation assays, PPD and PPT significantly improved the expression of type-I collagen, fibrillin-1, and elastin in human dermal fibroblasts from both young and old subjects; these were comparable with the effects of the SSF-P extracts. Overall, our results suggest that changes in the metabolites of P. notoginseng fermented with A. cristatus enhance the quality and availability of bioactive compounds associated with skin anti-aging.